2019
DOI: 10.3390/ma12050767
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bainite in Wear and Friction Behavior of Austempered Ductile Iron

Abstract: The austempered ductile iron was austenitized at 900 °C for 1 h and quenched in an isothermal quenching furnace at 380 °C and 280 °C, respectively. This paper aims to investigate the effects of bainite on wear resistance of austempered ductile iron (ADI) at different loads conditions. The micro-structure and phase composition of ADI was characterized and analyzed by metallographic microscope (OM), X-ray diffractometer (XRD) and scanning electron microscope (SEM) with energy dispersive spectroscopy (EDS). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The ferrite and carbide cannot change into austenite completely. The relatively high cooling rate for the quenching process inhibits the diffusion of carbon, which hinders the formation of the bull's-eye ferrite [16][17]. Compared with the normalized and quenched-tempered sample, only the fine lower bainite is observed in the isothermal-quenched samples.…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…The ferrite and carbide cannot change into austenite completely. The relatively high cooling rate for the quenching process inhibits the diffusion of carbon, which hinders the formation of the bull's-eye ferrite [16][17]. Compared with the normalized and quenched-tempered sample, only the fine lower bainite is observed in the isothermal-quenched samples.…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…Austempered ductile iron (ADI) has been the subject of numerous studies in the past in order to exploit its attractive combination of tensile strength, ductility, fatigue strength, and toughness [1][2][3]. The wear resistance of ADI is reported to be comparable with quenched and tempered ductile iron [4].…”
Section: Introductionmentioning
confidence: 99%
“…The authors measured the austenite content using XRD tests and reported that the austenite transforms with a loading effect, and lower bainite, which contains a higher amount of austenite, responds better to loading. 12 Zhang et al investigated the potential usage of dual-phase ADI as a candidate material for metro wheels and investigated wear mechanisms under rolling contact. 13 Furthermore, Polishetty et al reported that plastic deformation-based manufacturing techniques, such as machining, may also cause the transformation of austenite to martensite.…”
Section: Introductionmentioning
confidence: 99%